Tokenized property renting and trading using blockchain - Hossain, Md. Miraj; Ahmed, Kazi Sazid; Saha, Senjuti; Eshan, Kazi Tasmima; Akand, Tasmia (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2022.